Retrieval of target photorecombination cross sections from high-order harmonics generated in a macroscopic medium - Jin, Cheng; Le, Anh-Thu; Lin, C. D. (My University, 2009)
We investigate high-order harmonic generation (HHG) in a thin macroscopic medium by solving Maxwell’s equation using microscopic single-atom induced dipole moment calculated from the recently developed quantitative rescattering (QRS) theory. We show that macroscopic HHG yields calculated from QRS compared well with those obtained from solving the single-atom time-dependent Schrödinger equation but with great saving of computer time. We also show that macroscopic HHG can be expressed as a product of a “macroscopic wave packet” and the photorecombination cross section of the target gas. The latter enables us to extract target structure from the experimentally measured HHG spectra, thus paves the way to use few-cycle infrared lasers for time-resolved chemical imaging of transient molecules with few-femtosecond temporal resolution.